Voltametric behavior of platinized titanium electrodes - Velichenko, Alexander B.; Kasian, Olga; Luk'Yanenko, Tatiana; Shmychkova, Olesia B.; Demchenko, Pavlo Yu; Gladyshevskii, Roman E. (Journal of Chemistry and Technologies, 2019)
The method for the combined synthesis of dimensionally stable anodes with an active TixOy/Pt layer on the metallic titanium substrates is proposed it is based on electrolytical deposition of the thin layer of platinum on the substrate and the further thermal treatment in air, which allows one to control the composition and the properties of the obtained materials. The content of the platinum decreases from the surface to the substrate with an increase in the ratio of metallic titanium and TiO2. It has been determined that coatings with the content of the platinum of up to 8 mg per cm-2 are represented by the titanium which is almost completely coated with the platinum with cracks and cavities. Thermal treatment leads to significant changes in the surface morphology, because the Pt is distributed over the surface and in the bulk due to diffusion and sintering, as well it leads to the increasing of the degree of crystallinity. It has been shown that the semiconductor properties of the composite TixOy/Pt electrodes on a titanium substrate are caused by the formation of titanium dioxide, which is an n-type semiconductor. It has been established that with the increasing of platinum coating thickness and the temperature of treatment, the potential of flat zones and the number of carriers also increases. Anomalously high values of the slopes of the polarization curves are explained by the presence of a space charge zone in the semiconductor. The data obtained indicate the possibility of using the reduction peak of oxygen-containing platinum compounds on the inversion voltammogram as a correlation parameter for predicting the electrocatalytic activity of the thermally treated Ti/Pt electrodes in the oxygen transfer reactions.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Composites; Inversion voltammetry; Mott-Schottky approach; Platinized titanium